WILL “THE HAWK” MAKE THE MARKET RANDOM WALK? - Budiarso, Novi Swandari; Pontoh, Winston (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes. Objective of study is examining market efficiency in Indonesia under high interest rates issue.Research Methods. Observation period on Indonesia stock composite index starts from June 7, 2023 to February 29, 2024. Several procedures are applied in objective of hypothesis testing, which are: (1) mean difference test supported by Cohen's test and normality test by Anderson-Darling in terms of detecting how market returns differ in the two observation periods; (2) runs test runs test in terms of detecting the randomness of market returns after the risk-free rate; (3) ARIMA is supported by the Augmented Dickey-Fuller test in terms of detecting whether randomness is just noise (or white noise); and (4) variance ratio test in terms of confirming the results of runs test and ARIMA to determine whether the market returns are efficient or just a noise.Research Results and Findings. Consistent with efficient market hypothesis, findings show that the market condition during the effective interest rate period of 6% has higher returns, riskier, better risk-return trade-off, and less efficient. During that period, noise seemed to play a role in creating market gaps. This study concludes that monetary policy in maintaining high effective interest rates cannot determine whether the market is more efficient. As implication, the high effective interest rate tends not to result in a shift in investor behavior to allocate stock investments to risk-free assets. This study contributes to develop the finance and accounting science, especially in the fair presentation of financial information including investment decisions.